Implementasi Etika Pemasaran Syariah pada Bank Syariah Indonesia (BSI) KC S Parman 2 Kota Bengkulu - Hanisa Febianti; Desi Isnaini; Aan Shar (Universitas Batanghari Jambi, 2023)
Entrepreneurs expect profits from every sales movement. Islam sees profit not in the amount of profit obtained, but also in receiving Allah's favor and pleasure. Sharia promotional morals are standards that display standards that carry out promotional obligations in sharia. The purpose of this idea is to find out how to implement Islamic marketing ethics at Bank Syariah Indonesia KC S Parman 2 in the city of Bengkulu. This question is based on subjective case thinking about the use of field investigation strategies. Important information and additional information are used as sources of information. The information gathering method used in this consideration is through interviews, perceptions and documentation. From the results of this thinking, it can be concluded that the implementation of Islamic preaching morals by Bank Syariah Indonesia KC S. Parma 2 Bengkulu is very good, as evidenced by representatives who behave naturally, serve customers well and run well and full of affection. and act seriously.